Entrepreneurship Readiness Towards the Industrial Revolution 4.0 - Silvia Hendrayanti; Wachidah Fauziyanti (AIBPM Publisher, 2021)
In the 4.0 industry revolution, there are many entrepreneurial opportunities for those who can identify the existing business opportunities. However, the interest in entrepreneurship in Indonesia is still very low, this has led to the rise of unemployment. The cause of the increasing unemployment rate in Indonesia is the imbalance in the number of jobs with the number of graduates increasing every year. This research is proposed to determine the contribution of students' interest in entrepreneurship and self-efficacy to the readiness of students to become entrepreneurs towards the industrial revolution 4.0. The population in this study were university students in Semarang, especially the economics faculty who had taken entrepreneurship courses. This study took 97 samples of respondents. The analytical tool used is Structure Equation Models with Partial Least Square approach. The results showed that the students' interest in entrepreneurship had a positive and significant effect on entrepreneurial readiness with a coefficient value of 0.309. It means that the effect of interest in entrepreneurship on entrepreneurial readiness is 30.9%. Self-efficacy has a positive and significant effect on entrepreneurial readiness with a coefficient value of 0.655 which means the effect of self-efficacy on entrepreneurial readiness is 65.5%.